Seasonal variation of carrageenan yield, gel strength and viscosity in Sarcopeltis (ex Gigartina) skottsbergii from Southern Chile. Issue 1 (29th September 2021) - Westermeier, Renato; González, Carmen; Murúa, Pedro; Morales, Juan; Patiño, David J.; Fabres, Natacha; Zamorano, Jaime; Müller, Dieter G.
SUMMARY: Chile is one of the top carrageenan producers worldwide, and Sarcopeltis (ex Gigartina ) skottsbergii one of the topmost exploited carrageenophytes from the wild in the world. Total yield, gel strength and viscosity from two contrasting environments Calbuco and Ancud (Inner and Outer Sea, Chile) were estimated monthly in approximately 2 years for this species. While carrageenan yields did not show differences between localities, gametophytes in spring–summer had 15% higher, compared to tetrasporophytes. Sizes (frond surface) normally did not affect carrageenan yields. Gametophytes showed clear differences in gel strength between seasons, but not between localities, with maximum peaks during winter–spring months in Calbuco and autumn‐winter months in Ancud. Seasonal variations in viscosity were also significant. While gametophyte viscosity did not exceed 120 cPs, tetrasporophytes reached 1400 cPs in Calbuco and 1000 cPs in Ancud. More remarkably, a positive correlation between viscosity and gel strength was found in S. skottsbergii gametophytes, which is significantly different between both localities. These results suggest that selective harvesting in spring–summer should be preferred to optimize cost–benefit of harvesting activities and subsequent carrageenan productivity.